Physical Activity Levels, Perceived Body Appearance, and Body Functioning in Relation to Perceived Wellbeing Among Adolescents - Sollerhed, Ann-Christin; Fransson, Johanna; Skoog, JIsabelle; Garmy, Pernilla (Frontiers in Sports and Active Living, 2022)
This study aimed to investigate self-reported physical activity levels, perceived body appearance, and body functioning in relation to perceived well-being among adolescents. A cross-sectional survey was performed in four upper secondary schools in one municipality in southern Sweden. Data were obtained from questionnaires completed by 1491 adolescents (55.4% females; median age 16; range 15–17 years) during school hours. The participation rate was 71.4%. Logistic regression analyses were carried out with well-being as the dependent variable. The independent variables included gender, perceived family financial situation, perceived body appearance, perceived body function, and physical activity level. Perceived positive well-being was associated with being satisfied with their body’s appearance (OR 3.4; CI 2.6–4.4) and function (OR 3.1; CI 2.2–4.2), being physically active three or more times per week (OR 1.5; CI 1.1–2.0), and a good perceived family financial situation (OR 3.3; CI 1.6–6.7). Gender was not significantly associated with well-being. A positive body image, which include both body appearance and body function, and high physical activity levels were significantly associated with well-being in adolescents, corroborating the importance of promoting physical activity among younger populations.